HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN PENYESUAIAN DIRI PEREMPUAN PADA KEHAMILAN PERTAMA - Arini Budi Astuti; Singgih Wibowo Santosa; Muhana Sofiati Utami (Jurnal Psikologi, 2000)
Substantial physical and emotional changes happen during pregnancy. Even though pregnancy is only a short periode in woman’s life, it determines the physical and psychological quality not only for pregnant woman herself but also for the baby. Pregnant women who are able to develop appropriate adjustment during pregnancy can manage the challenges and changes that happen, so the physical and psychological well being of the mother and baby can be maintained. This research sets out to understand how far the relationship between family support and women’s adjustment during their first pregnancy . The hypothesis is: there is a positive relationship between family support and women’s adjustment during their first pregnancy. Subjects of this research were 56 women who underwent their first pregnancy (primigravida). The subjects came from three Public Health Centres of Yogyakarta municipality. Those Public Health Centers were Tegalrejo, Jetis, and Pakulaman. Data were collected by using Family Support Scale which contains 45 items and Adjustment Scale which contains 35 items. Both of the scales had been tested on 40 respondents that had the same characteristics with research subjects. The respondents were from Mergangsan, Danurejan II, and Umbulharjo II Public Health Centres. The result shows positive correlation between family support and women’s adjustment. The correlation coeffisien (r) is 0,7311 ; p < 0,01 and the determination coefficient (r2) is 0,5346. It means that the research hypothesis is supported by the result of the data analysis. Keyword: family support, adjustment, first pregnancy